Contrasting effects of comorbidities on emergency colon cancer diagnosis: a longitudinal data-linkage study in England - Renzi, Cristina; Lyratzopoulos, Georgios; Hamilton, Willie; Maringe, Camille; Rachet, Bernard (BMC health services research, 2019)
Background One in three colon cancers are diagnosed as an emergency, which is associated with worse cancer outcomes. Chronic conditions (comorbidities) affect large proportions of adults and they might influence the risk of emergency presentations (EP). Methods We aimed to evaluate the effect of specific pre-existing comorbidities on the risk of colon cancer being diagnosed following an EP rather than through non-emergency routes. The cohort study included 5745 colon cancer patients diagnosed in England 2005–2010, with individually-linked cancer registry, primary and secondary care data. In addition to multivariable analyses we also used potential-outcomes methods. Results Colon cancer patients with comorbidities consulted their GP more frequently with cancer symptoms during the pre-diagnostic year, compared with non-comorbid cancer patients. EP occurred more frequently in patients with ‘serious’ or complex comorbidities (diabetes, cardiac and respiratory diseases) diagnosed/treated in hospital during the years pre-cancer diagnosis (43% EP in comorbid versus 27% in non-comorbid individuals; multivariable analysis Odds Ratio (OR), controlling for socio-demographic factors and symptoms: men OR = 2.40; 95% CI 2.0–2.9 and women OR = 1.98; 95% CI 1.6–2.4. Among women younger than 60, gynaecological (OR = 3.41; 95% CI 1.2–9.9) or recent onset gastro-intestinal conditions (OR = 2.84; 95% CI 1.1–7.7) increased the risk of EP. In contrast, primary care visits for hypertension monitoring decreased EPs for both genders. Conclusions Patients with comorbidities have a greater risk of being diagnosed with cancer as an emergency, although they consult more frequently with cancer symptoms during the year pre-cancer diagnosis. This suggests that comorbidities may interfere with diagnostic reasoning or investigations due to ‘competing demands’ or because they provide ‘alternative explanations’. In contrast, the management of chronic risk factors such as hypertension may offer opportunities for earlier diagnosis. Interventions are needed to support the diagnostic process in comorbid patients. Appropriate guidelines and diagnostic services to support the evaluation of new or changing symptoms in comorbid patients may be useful.